An Analysis on the EFL Teachers’ Perception about Authentic Assessment - Imansyah, Imansyah; Utama, I Made Permadi; Sumarni, Baiq (VELES Voices of English Language Education Society, 2018)
This research was aimed in attempt to analyze and describe the EFL Teachers’ Perception about Authentic Assessment. The EFL teachers at MA DI PUTRA NURUL HAKIM were taken as subjects of this research. Descriptive research design with quantitative data was applied since the method of gathering the data was questionnaire with interview as the supporting method. In relation to the problem proposed, the current study found that the EFL teachers at MA DI PUTRA NURUL HAKIM had positive perception about authentic assessment. It was proven that the EFL teachers had positive knowledge, point of view, belief, feeling, and behaviour towards authentic assessment.